A influência da modernização do sistema de controle de trens no consumo de energia no metrô de São Paulo - Gomes, Francisco Moraes (2017)
The aim of this research is to study the potential association between the reduction in electricity consumption in Line 2 – Green of the São Paulo Subway and the change of the Train Control System from the "fixed block" type to the "moving block" type. This study is necessary because the transport sector is one of the biggest consumers of energy and the energy is one of the highest costs of the metro system, so that any reduction must be studied and understood. Most of the previous studies published on energy efficiency at subways and trains are simulation studies, there is a few literature based on empirical data. The statistical approach was chosen because there is no installed equipment to directly measure this influence, since there are only measures of consumption at the entrances of the System and there is no individual measurement of each train. Part of the data used was obtained via official communication channels of the company, another part was obtained directly from the operational reports and other data was extracted from the capture of the communications between the trains and centralized control system. Several variables that can influence the consumption of the line and also the train speed profiles in the periods just before and after the System change have been verified. The study of the relationships among these variables was done and the multivariate regression analysis was performed. The results of the regression generated an equation model with significance for the variables: type of system, proportion of useof the fleets used and the number of trips made. In the regression process, the stepwise method was used and some variables were withdrawn when verifying that they had multicollinearity. The data extracted from the communication protocol were not used in the regression, but they did allow verifying an evidence of improvement in the speed profiles and also a reduction in the number of stops that the train made in the route, indicating a smaller interference between the train movements with the new system. The calculated savings obtained by the new system was around 2.8%, rising to about 7.8% on average when the new fleet was included, which only uses the "moving block" system.